Most eGovernment-for-Development Projects Fail:How Can Risks be Reduced? - RICHARD HEEKS (Institute for Development Policy and Management, 2003)
eGovernment can make a valuable contribution to development. However, at present, the majority of e-government-for-development projects fail either totally or partially. This paper explains the underlying cause of failure: the oversize gaps between project design and on-the-ground reality (known as 'design-reality gaps'). The dimensions of these gaps are identified, as are archetypal situations in which failure is likely to occur. The paper then provides a step-by-step guide to identifying and addressing failure risks for e-government projects. It concludes with a real-world case study of using the design-reality gap approach to reduce risks in an e-government project.